2013
DOI: 10.5551/jat.14837
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between a Mediterranean Diet and Circulating Adiponectin Levels is Influenced by Cigarette Smoking

Abstract: Aim: Adherence to a Mediterranean diet has been shown to lower the risk of developing several chronic diseases. The ability to augment circulating adiponectin levels is proposed as an underlying mechanism mediating the beneficial effects of this diet. We aimed to examine whether the positive relationship between the Mediterranean diet and adiponectin is altered by cigarette smoking, taking potential confounders into consideration. Methods: Plasma adiponectin levels were enzymatically measured in 45 never smoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…Adiponectin levels may be negatively influenced by lifestyle, such as sedentarism, a high-fat diet causing obesity, or excessive smoking [94]. This influence can be reversed; lifestyle correction helps to favorably modify plasma adiponectin levels.…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin levels may be negatively influenced by lifestyle, such as sedentarism, a high-fat diet causing obesity, or excessive smoking [94]. This influence can be reversed; lifestyle correction helps to favorably modify plasma adiponectin levels.…”
Section: Introductionmentioning
confidence: 99%
“…Adiponectin levels have been shown to be increased due to reduced renal function [33][34][35] and decreased by cigarette smoking 36) . Reduced renal function would decrease the clearance of adiponectin, resulting in an increase in circulating adiponectin levels, even in the healthy subjects.…”
Section: Sem Analysis Of the Effects Of Snps On Adiponectin Levels Anmentioning
confidence: 99%
“…Moreover, we did not collect information about smoking habits of the studied women. This might influence our results, because recently it has been suggested that circulating adiponectin levels are negatively associated with smoking .…”
Section: Discussionmentioning
confidence: 90%